Composite powder as well as preparation method and application thereof
Through the mutual attraction between modified carbon black and array carbon nanotubes, the problems of poor conductivity and complex carbon nanotube processes are solved, and a composite powder with high conductivity and simple processes are realized. It is suitable for lithium-ion batteries. Conductive agent.
Patent Information
- Application Number
- CN202411345939.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The conductive agent of existing lithium-ion batteries has poor conductivity and high addition amount. Carbon nanotubes need to be added in the form of slurry, which is complicated in the process.
Modified carbon black and modified array carbon nanotubes are used to form modified carbon black with negative charges on the surface and modified array carbon with positive charges on the surface. Nanotubes attract each other to improve dispersion and conductivity and reduce carbon black usage.
The conductive properties and dispersion of the composite powder are improved, so that it can be directly added to the system in the form of powder, with a simple process and convenient industrial production.
Smart Images

Figure CN119324229A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of material technology, and specifically relates to a composite powder and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have broad application prospects in portable electronic devices and electric vehicles due to their high operating voltage, large specific capacity, stable discharge, small size, light weight, no memory effect, high safety, long life and environmental friendliness. Conductive agents are often used in the positive and negative pole pieces of lithium-ion batteries. Conductive agents can improve the activity of pole piece materials, thereby improving the performance of lithium-ion batteries.
[0003] Common conductive agents currently used in lithium-ion batteries include conductive carbon black, carbon nanotubes and graphene. Among them, the advantage of conductive carbon black is that it can be added to the material of the pole piece in the form of powder, and the process is simple and easy to operate. The disadvantage is that the conductive carbon black has poor conductivity and a high addition amount (generally the addition amount needs to reach 5-10%, because a low addition amount will lead to a low capacity of the lithium-ion battery); while the advantage of carbon nanotubes is good conductivity, low addition amount, and can improve the capacity and rate performance of lithium-ion batteries. The disadvantage is that it needs to be added to the pole piece material in the form of slurry, and the process is complicated.
[0004] Therefore, it is necessary to provide a conductive agent with good conductivity, low addition amount and simple process. Summary of the invention
[0005] The purpose of the present application is to overcome the above-mentioned deficiencies of the prior art and to provide a composite powder and a preparation method and application thereof, so as to solve the problems of poor conductivity and high addition amount of the existing conductive carbon black as a conductive agent, as well as the problems of carbon nanotubes as a conductive agent that need to be made into slurry and the complex process.
[0006] In order to achieve the above application objectives, the first aspect of the present application provides a composite powder, including:
[0007] Modified carbon black, wherein the modified carbon black is obtained by the following steps: mixing carbon black with an acid solution and treating it to obtain acidified carbon black, adding the acidified carbon black into an anionic surfactant aqueous solution and treating it to obtain anionic surfactant-modified carbon black, dispersing the anionic surfactant-modified carbon black in a first salt solution and treating it to obtain modified carbon black with a negative charge on the surface;
[0008] Modified array carbon nanotubes, wherein the modified array carbon nanotubes are obtained by the following steps: mixing array carbon nanotubes with acid solution and treating them to obtain acidified array carbon nanotubes, adding the acidified array carbon nanotubes into an aqueous solution of a coupling agent containing amino groups and treating them to obtain carbon nanotubes modified by the coupling agent containing amino groups, dispersing the carbon nanotubes modified by the coupling agent containing amino groups in a second salt solution and treating them to obtain modified array carbon nanotubes with positive charges on the surface;
[0009] The negative charges in the modified carbon black are used to attract the positive charges in the modified array carbon nanotubes.
[0010] Further, the mixing and treating of carbon black with acid solution to obtain acidified carbon black comprises:
[0011] Selecting conductive carbon black with a particle size range of 100-20000nm;
[0012] The conductive carbon black is placed in an acid solution with a molar concentration range of 0.7-1.2 mol / L, pretreated at 70-100° C. for 1-3 hours, filtered and washed until the filtrate is neutral, and then dried at 110-130° C. for 19-24 hours to obtain the acidified carbon black.
[0013] Further, the step of adding the acidified carbon black to an anionic surfactant aqueous solution and treating it to obtain anionic surfactant-modified carbon black, and dispersing the anionic surfactant-modified carbon black in a first salt solution and treating it to obtain a modified carbon black with a negative charge on the surface comprises:
[0014] The acidified carbon black is placed in an aqueous solution of an anionic surfactant with a concentration range of 0.003-0.008 g / mL, and ultrasonically treated at a frequency of 10-30 Hz for 0.2-0.7 h. After stirring the solution at a stirring speed range of 100-300 r / min for 1-4 h, the solution is placed in a water bath at 20-40° C. and allowed to stand for 2-6 h. The solution is filtered and washed, and then dispersed in a 0.0005-0.003 M salt solution, and ultrasonically treated at a frequency of 10-30 Hz for 0.1-2 h to obtain the modified carbon black with a negative charge on the surface.
[0015] Furthermore, the step of mixing the array carbon nanotubes with an acid solution and treating the mixture to obtain the acidified array carbon nanotubes comprises:
[0016] Selecting array carbon nanotubes with an aspect ratio ranging from 5000 to 15000 and a Raman spectrum intensity ratio ranging from 0.8 to 1.3;
[0017] The array carbon nanotubes are placed in an acid solution for treatment, and then filtered, washed and dried to obtain the acidified array carbon nanotubes.
[0018] Further, the acidified array carbon nanotubes are added to an aqueous solution of an amino-containing coupling agent and treated to obtain carbon nanotubes modified with an amino-containing coupling agent, and the carbon nanotubes modified with an amino-containing coupling agent are dispersed in a second salt solution and treated to obtain modified array carbon nanotubes with positive charges on the surface, including:
[0019] The acidified carbon nanotubes are added to an aqueous solution of an amino-containing coupling agent, and ultrasonically treated at a frequency of 20-100 Hz for 0.5-24 hours, and stirred at a stirring speed range of 200-4000 r / min for 2-24 hours, and the solution containing the acidified array carbon nanotubes and the amino-containing coupling agent is placed in a 35-70° C. water bath for 4-24 hours, and then dried after multiple centrifugations to obtain carbon nanotubes modified with an amino-containing coupling agent;
[0020] The carbon nanotubes modified by the amino-containing coupling agent are dispersed in a salt solution with a molar mass range of 0.001-2M, and ultrasonically treated at a frequency of 20-100 Hz for 0.5-2 hours to obtain the modified array carbon nanotubes with positive charges on the surface.
[0021] Furthermore, the mass ratio of the modified carbon black to the modified array carbon nanotubes is in the range of 90-98:2-10.
[0022] Furthermore, the oil absorption of the composite powder is in the range of 120-220 mg / 100 g;
[0023] and / or,
[0024] The resistivity of the composite powder is in the range of 80-140 mΩ·cm;
[0025] and / or,
[0026] The specific surface area of the composite powder is in the range of 50-150 m 2 / g.
[0027] A second aspect of the present application provides a lithium-ion battery comprising the above-mentioned composite powder.
[0028] The third aspect of the present application provides a method for preparing the above-mentioned composite powder, comprising the following steps:
[0029] The modified carbon black and the modified array carbon nanotubes are mixed and pulverized to obtain the composite powder.
[0030] Furthermore, the mixture of the modified carbon black and the modified array carbon nanotubes is pulverized by using air flow pulverizing equipment.
[0031] Compared with the prior art, this application has the following technical effects:
[0032] The composite powder and its preparation method and application provided in the embodiments of the present application are composed of modified carbon black with negative charge and modified array carbon nanotubes with positive charge. The positive and negative charges attract each other, which can improve the dispersion performance of array carbon nanotubes and carbon black in the composite powder and improve the conductivity of the composite powder. At the same time, the modified array carbon nanotubes can reduce the amount of modified carbon black while improving the conductivity of the composite powder. In addition, when the composite powder is used as a conductive agent, it can be directly added to the system in the form of powder and is very easy to disperse into various systems, that is, a mixed powder of carbon black and carbon nanotubes is directly obtained. The process is simple and easy to operate, which is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0034] Figure 1 This is a process flow chart of preparing a carbon black having a negative charge on the surface provided in an embodiment of the present application;
[0035] Figure 2 This is a process flow chart of preparing an array of carbon nanotubes with positive charges on the surface provided in an embodiment of the present application;
[0036] Figure 3 is a process flow chart of preparing a composite powder provided in an embodiment of the present application;
[0037] Figure 4 It is a structural schematic diagram of an air flow pulverizing device provided in an embodiment of the present application. DETAILED DESCRIPTION
[0038] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0039] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0040] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all mean: a, b, c, ab (i.e. a and b), ac, bc or abc, where a, b, c can be single or multiple, respectively.
[0041] It should be understood that in the various embodiments of the present application, the size of the serial number of each process does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0042] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0043] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass in the embodiment description of the present application can be a well-known mass unit such as μg, mg, g, kg, etc.
[0044] The terms "first", "second", etc. are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, a feature defined as "first", "second", etc. may explicitly or implicitly include one or more of the features.
[0045] In a first aspect, the embodiments of the present application provide a method for preparing a composite powder with high dispersibility and high conductivity.
[0046] like Figure 1 As shown, the present invention provides a method for preparing modified carbon black, comprising the following steps:
[0047] S11. Select conductive carbon black.
[0048] In applications, the conductive carbon black may be N326 or the like.
[0049] The resistivity of the conductive carbon black may be in the range of 0.2-50Ω·cm. For example, the resistivity of the conductive carbon black may be 0.2Ω·cm, 1Ω·cm, 10Ω·cm, 20Ω·cm, 30Ω·cm or 50Ω·cm.
[0050] The particle size of the conductive carbon black powder may range from 100 to 20000 nm.
[0051] S12. Place the conductive carbon black in an acid solution, treat it at a pretreatment temperature for a period of time, filter and wash until the filtrate is neutral, and dry to obtain carbon black purified by the acid solution.
[0052] In the application, the acid solution may include hydrochloric acid (HCl), sulfuric acid (H 2 SO 4 ) and nitric acid (H 3 PO 4 ) and the like. Preferably the acid solution is concentrated HCl, concentrated H 2 SO 4 He Cong H 3 PO 4 A combination of one or more of the following, wherein concentrated HCl refers to a hydrochloric acid solution with a mass fraction of HCl exceeding 20%. 2 SO 4 It means H 2 SO 4 The mass fraction of sulfuric acid is greater than or equal to 70%, and the concentrated H 3 PO 4 Generally refers to H 3 PO 4 Nitric acid solution above 8 mol / L.
[0053] The molar concentration of the acid solution may range from 0.7 to 1.2 mol / L. For example, the molar concentration of the acid solution may be 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L or 1.2 mol / L, etc.
[0054] The above-mentioned pretreatment temperature range can be 70-100℃, and the pretreatment time range can be 1-3h. Exemplarily, the pretreatment temperature can be 70℃, 80℃, 85℃, 90℃, 95℃ or 100℃, etc., and the pretreatment time can be 1h, 1.5h, 2h, 2.5h, 2.8h or 3h, etc.
[0055] The drying temperature may range from 110 to 130° C., and the drying time may range from 19 to 24 hours. For example, the drying temperature may be 110° C., 115° C., 120° C., 123° C., 128° C. or 130° C., and the drying time may be 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours, etc.
[0056] Therefore, the metal impurities, ash, etc. in the conductive carbon black can be removed by acid treatment, and the surface functional groups and defects of the conductive carbon black can be increased, thereby improving the dispersibility of the conductive carbon black. At the same time, since the acid treatment can increase the active sites on the surface of the conductive carbon black, the anionic surfactant in the subsequent steps can be more easily adsorbed on the surface of the conductive carbon black treated with acid purification, making the conductive carbon black treated with acid purification more easily react with the anionic surfactant.
[0057] S13. Add the carbon black purified by acid solution into an aqueous solution of anionic surfactant, ultrasonically treat and stir at a certain speed for a period of time, then place the solution in a water bath at a certain temperature and let it stand for a period of time to obtain an aqueous solution of carbon black non-covalently modified by anionic surfactant, and then filter, wash and dry the aqueous solution of carbon black non-covalently modified by anionic surfactant in turn to obtain carbon black non-covalently modified by anionic surfactant.
[0058] In applications, the anionic surfactant may include one or more combinations of polystyrene sulfonate (Poly (sodium-p-styrenesulfonate), PSS), sodium dodecyl sulfate (Sodium Dodecyl Sulfate, SDS), sodium hexadecyl benzene sulfonate (Sodium Dodecyl Benzene Sulfonate, SDBS), etc.
[0059] The concentration range of the anionic surfactant can be 0.003-0.008 g / mL. For example, the concentration of the anionic surfactant can be 0.003 g / mL, 0.004 g / mL, 0.005 g / mL, 0.006 g / mL, 0.007 g / mL or 0.008 g / mL, etc.
[0060] The mass volume ratio of the carbon black purified by acid to the aqueous solution of anionic surfactant can range from 1g:8mL to 1g:13mL. For example, the mass volume ratio of the carbon black purified by acid to the aqueous solution of anionic surfactant can be 1g:8mL, 1g:9mL, 1g:10mL, 1g:11mL, 1g:12mL or 1g:13mL, etc. Preferably, the mass volume ratio of the carbon black purified by acid to the aqueous solution of anionic surfactant is 1:10. At this time, the surface treatment effect of the carbon black purified by acid is better.
[0061] An ultrasonic device can be used for ultrasonic treatment, wherein the ultrasonic frequency range can be 10-30 Hz, and the ultrasonic treatment time range can be 0.2-0.7 h. Exemplarily, the ultrasonic frequency can be 10 Hz, 15 Hz, 20 Hz, 25 Hz, 28 Hz or 30 Hz, and the ultrasonic treatment time can be 0.2 h, 0.3 h, 0.4 h, 0.5 h, 0.6 h or 0.7 h, etc.
[0062] The solution can be stirred by magnetic stirring or electric stirring, wherein the stirring time range can be 1-4h, and the stirring speed range can be 100-300r / min. Exemplarily, the stirring time can be 1h, 1.5h, 2h, 2.5h, 3h or 4h, and the stirring speed can be 100r / min, 150r / min, 200r / min, 250r / min, 280r / min or 300r / min, etc.
[0063] A water bath can be used for water bathing, wherein the water bath temperature range can be 20-40°C, and the standing time in the water bath can range from 2-6h. Exemplarily, the water bath temperature can be 20°C, 25°C, 30°C, 33°C, 38°C or 40°C, etc., and the standing time in the water bath can be 2h, 3h, 4h, 4.5h, 5h or 6h, etc.
[0064] Therefore, in the reaction between the anionic surfactant and the carbon black purified by acid, the anionic surfactant can be adsorbed on the surface of the carbon black particles purified by acid, so that the surface of the carbon black purified by acid has a negative charge and the dispersibility of the carbon black is improved.
[0065] S14. The carbon black modified by non-covalent bonds of anionic surfactant is dispersed in a salt solution and ultrasonically treated for a period of time to obtain carbon black with negative charge on the surface.
[0066] In applications, the salt in the above-mentioned salt solution may be sodium chloride (NaCl) or the like.
[0067] The molar mass of the salt solution may range from 0.0005 to 0.003 M. For example, the molar mass of the salt solution may be 0.0005 M, 0.001 M, 0.0015 M, 0.002 M, 0.0025 M or 0.003 M, etc.
[0068] The dispersion concentration range of the carbon black non-covalently modified by anionic surfactant in the salt solution can be 0.001-0.03 mg / mL. For example, the dispersion concentration of the carbon black non-covalently modified by anionic surfactant in the salt solution can be 0.001 mg / mL, 0.01 mg / mL, 0.015 mg / mL, 0.02 mg / mL, 0.025 mg / mL or 0.03 mg / mL, etc.
[0069] An ultrasonic device can be used for ultrasonic treatment, wherein the ultrasonic frequency range can be 10-30 Hz, and the ultrasonic treatment time range can be 0.1-2 h. Exemplarily, the ultrasonic frequency can be 10 Hz, 15 Hz, 20 Hz, 25 Hz, 28 Hz or 30 Hz, and the ultrasonic treatment time can be 0.1 h, 0.5 h, 1 h, 1.3 h, 1.7 h or 2 h, etc.
[0070] Thus, the salt solution can further improve the dispersibility of the carbon black modified by the non-covalent bond of the anionic surfactant and form a stable dispersion system.
[0071] The specific preparation method of carbon black with negative charge on the surface (i.e. modified carbon black) is given below, and the preparation method comprises the following steps:
[0072] (1). Selection and pretreatment of carbon black:
[0073] Conductive carbon black with a powder particle size of 100-20000nm is selected, placed in an acid solution with a molar concentration of 0.7-1.2mol / L, pretreated at 70-100°C for 1-3h, filtered and washed until the filtrate is neutral, and then dried at 110-130°C for 19-24h to obtain carbon black purified by acid solution.
[0074] (2). Carbon black surface treatment:
[0075] The carbon black purified by acid solution is added to an anionic surfactant aqueous solution with a concentration of 0.003-0.008 g / mL (the mass volume ratio of the carbon black purified by acid solution to the anionic surfactant aqueous solution is 1:8-1:13), and ultrasonic treatment is performed at a frequency of 10-30 Hz for 0.2-0.7 h using an ultrasonic device, and the solution is stirred for 1-4 h at a stirring speed of 100-300 r / min using room temperature magnetic stirring or electric stirring, and then the solution is placed in a water bath at 20-40° C. and allowed to stand for 2-6 h to obtain an anionic surfactant non-covalently modified carbon black aqueous solution, which is then filtered and washed to obtain an anionic surfactant non-covalently modified carbon black.
[0076] (3). Preparation of modified carbon black:
[0077] The carbon black non-covalently modified with anionic surfactant is dispersed in a 0.0005-0.003M salt solution (the dispersion concentration of carbon black in the salt solution is 0.001-0.03 mg / mL), and ultrasonically treated with a 10-30 Hz ultrasonic device for 0.1-2 h to obtain carbon black with a negative charge on the surface.
[0078] Then, if Figure 2 As shown, the present invention provides a method for preparing a modified array carbon nanotube, comprising the following steps:
[0079] S21. Selecting an array of carbon nanotubes and subjecting the array of carbon nanotubes to an acid treatment to obtain an acid-purified array of carbon nanotubes.
[0080] In applications, the aspect ratio of the array carbon nanotubes may be in the range of 5000 to 15000. The aspect ratio of the array carbon nanotubes is relatively high, and it is easier to form a conductive path, thereby improving the conductive properties of the composite powder.
[0081] The Raman spectrum intensity ratio of the arrayed carbon nanotubes may be in the range of Raman ID / IG from 0.8 to 1.3.
[0082] Acids can include hydrochloric acid (HCl), sulfuric acid (H 2 SO 4 ) and nitric acid (H 3 PO 4 ) and the like. Preferably the acid solution is concentrated HCl, concentrated H 2 SO 4 He Cong H 3 PO 4 One or more combinations of the above.
[0083] Thus, the array carbon nanotubes can be modified by acid treatment, and some specific functional groups can be introduced on the surface of the carbon nanotubes, and these functional groups can chemically react with the amino-containing silane coupling agent in the subsequent steps.
[0084] S22. Add the acid-purified array carbon nanotubes to an aqueous solution of an amino-containing coupling agent, ultrasonically treat the solution, stir the solution at a certain speed for a period of time, place the solution in a water bath at a certain temperature and let it stand for a period of time to obtain a uniformly dispersed aqueous solution of array carbon nanotubes, centrifuge it several times and then dry it to obtain array carbon nanotubes modified with an amino-containing coupling agent.
[0085] In applications, the amino-containing coupling agent may include an amino-containing silane coupling agent, for example, aminotriethoxysilane (APTES), γ-aminopropyltriethoxysilane (KH-550), and the like.
[0086] Therefore, by modifying the array carbon nanotubes with the amino-containing coupling agent, the dispersion uniformity of the modified array carbon nanotubes can be improved.
[0087] The mass volume ratio of the arrayed carbon nanotubes treated with acid purification to the amino-containing coupling agent aqueous solution can range from 1g:10mL to 1g:150mL. For example, the mass volume ratio of the arrayed carbon nanotubes treated with acid purification to the amino-containing coupling agent aqueous solution can be 1g:10mL, 1g:50mL, 1g:80mL, 1g:100mL, 1g:120mL or 1g:150mL, etc.
[0088] The concentration of the amino-containing coupling agent in the coupling agent solution may range from 0.01 to 10 wt %. For example, the concentration of the amino-containing coupling agent in the coupling agent solution may be 0.01 wt %, 0.1 wt %, 1 wt %, 3 wt %, 6 wt % or 10 wt %, etc.
[0089] An ultrasonic device can be used for ultrasonic treatment, wherein the ultrasonic frequency range can be 20-100 Hz, and the ultrasonic treatment time range can be 0.5-24 h. Exemplarily, the ultrasonic frequency can be 20 Hz, 40 Hz, 60 Hz, 70 Hz, 80 Hz or 100 Hz, and the ultrasonic treatment time can be 0.5 h, 1 h, 10 h, 15 h, 20 h or 24 h, etc.
[0090] The solution can be stirred by magnetic stirring or electric stirring, wherein the stirring speed range can be 200-4000r / min, and the stirring time range can be 2-24h. Exemplarily, the stirring speed can be 200r / min, 700r / min, 1000r / min, 2000r / min, 3000r / min or 4000r / min, and the stirring time can be 2h, 7h, 12h, 18h, 20h or 24h, etc.
[0091] A water bath can be used for water bathing, wherein the water bath temperature range can be 35-70°C, and the standing time in the water bath can range from 4-24h. Exemplarily, the water bath temperature can be 35°C, 40°C, 50°C, 60°C, 65°C or 70°C, etc., and the standing time in the water bath can be 4h, 7h, 10h, 15h, 20h or 24h, etc.
[0092] Therefore, in the reaction between the amino-containing coupling agent and the carbon nanotubes purified by acid, the amino groups in the coupling agent can react with the functional groups on the surface of the acid-purified carbon nanotubes to form chemical bonds, which can improve the dispersion performance of the carbon nanotubes, enhance the compatibility of the carbon nanotubes, and introduce hydrophilic groups on the surface of the carbon nanotubes, thereby improving the performance of the array carbon nanotubes modified by the amino-containing coupling agent.
[0093] S23. Dispersing the array carbon nanotubes modified with the amino-containing coupling agent in a salt solution, and subjecting the solution to ultrasonic treatment for a period of time, to obtain the array carbon nanotubes with positive charges on the surface.
[0094] In the application, the salt in the above-mentioned salt solution can be NaCl, potassium chloride (KCl), calcium chloride (CaCl 2 ) etc.
[0095] The molar mass of the salt solution may range from 0.001 to 2 M. For example, the molar mass of the salt solution may be 0.001 M, 0.01 M, 0.1 M, 1 M, 1.5 M or 2 M, etc.
[0096] The dispersion concentration range of the array carbon nanotubes modified with the amino-containing coupling agent in the salt solution can be 0.01-10 mg / mL. Exemplarily, the dispersion concentration of the array carbon nanotubes modified with the amino-containing coupling agent in the salt solution can be 0.01 mg / mL, 0.1 mg / mL, 1 mg / mL, 3 mg / mL, 6 mg / mL or 10 mg / mL, etc.
[0097] An ultrasonic device can be used for ultrasonic treatment, wherein the ultrasonic frequency range can be 20-100 Hz, and the ultrasonic treatment time range can be 0.5-2 h. Exemplarily, the ultrasonic frequency can be 20 Hz, 30 Hz, 50 Hz, 70 Hz, 80 Hz or 100 Hz, and the ultrasonic treatment time can be 0.5 h, 0.7 h, 0.8 h, 1.0 h, 1.5 h or 2 h, etc.
[0098] Thus, the salt solution can further improve the dispersion performance of the array carbon nanotubes modified by the amino-containing coupling agent and form a stable dispersion system.
[0099] The following is a specific method for preparing carbon nanotubes with positive charges on the surface (i.e., modified array carbon nanotubes), which comprises the following steps:
[0100] (1). Surface treatment of carbon nanotubes:
[0101] The array carbon nanotubes treated with acid purification are added to an aqueous solution of an amino-containing coupling agent (the mass volume ratio of the array carbon nanotubes treated with acid purification to the aqueous solution of the amino-containing coupling agent is 1:10-1:150, and the concentration of the amino-containing coupling agent is 0.01-10wt%), and ultrasonic treatment is performed at 20-100Hz for 0.5-24h, followed by magnetic stirring or electric stirring for 2-24h at a stirring speed of 200-4000r / min, and the solution is placed in a water bath at 35-70°C and allowed to stand for 4-24h to obtain a uniformly dispersed array carbon nanotube aqueous solution, which is centrifuged several times and then dried to obtain array carbon nanotubes modified with an amino-containing coupling agent.
[0102] (2). Preparation of modified array carbon nanotubes:
[0103] The array carbon nanotubes modified with the amino-containing coupling agent are dispersed in a 0.001-2M salt solution (the dispersion concentration of the array carbon nanotubes modified with the amino-containing coupling agent in the salt solution is 0.01-10 mg / mL), and then ultrasonically treated at 20-100 Hz for 0.5-2 h to obtain array carbon nanotubes with positive charges on the surface.
[0104] It should be noted that there is no specific limitation on the preparation order of the modified carbon black and the modified array carbon nanotubes. The modified carbon black can be prepared first and then the modified array carbon nanotubes; or, the modified array carbon nanotubes can be prepared first and then the modified carbon black; or, the modified carbon black and the modified array carbon nanotubes can be prepared at the same time.
[0105] Finally, if Figure 3 As shown, the present application embodiment provides a method for preparing a composite powder, comprising the following steps:
[0106] S1. Carbon black with a negative charge on the surface and array carbon nanotubes with a positive charge on the surface are mixed and crushed to obtain a composite powder.
[0107] Figure 4 A schematic diagram of the structure of a jet milling device is shown. Figure 4 As shown, the air flow pulverizing equipment includes a mixing mechanism 1, a gas pulverizer 2, a first cyclone separator 3 and a second cyclone separator 4 which are connected in sequence through pipelines. The mixing mechanism 1 includes a frame 5, on which a tank body 6 is rotatably provided. The upper end of the tank body 6 is provided with a feed inlet for inputting a mixture of carbon black with negative surface charge and array carbon nanotubes with positive surface charge and a medium. A plurality of stirring mechanisms are provided inside the tank body 6. The discharge port of the first cyclone separator 3 is provided with a first collecting tank 7 for collecting the medium. The discharge port of the second cyclone separator 4 is provided with a second collecting tank 8 for collecting the mixture of carbon black with negative surface charge and array carbon nanotubes with positive surface charge after pulverization.
[0108] During operation, the carbon black with negative charge on the surface and the array carbon nanotubes with positive charge on the surface are mixed and fed into the tank 6 of the mixing mechanism 1 through the feed port. Under the action of the mixing mechanism 1, the fully mixed raw materials enter the gas pulverizer 2 to be pulverized. After pulverization, the first cyclone separator 3 collects the medium, and the second cyclone separator 4 collects the pulverized carbon nanotubes.
[0109] Among them, the medium can be chromium oxide (Cr 2 O 3 ), the gas pulverizer 2 can use 2-6 times supersonic airflow for pulverization.
[0110] In applications, the maximum particle size Dmax of the prepared composite powder is less than or equal to 50 nm. For example, the maximum particle size of the composite powder may be 20 nm, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm.
[0111] The preparation method of the composite powder provided in the embodiment of the present application, on the one hand, selects array carbon nanotubes with a high aspect ratio and uses them to modify carbon black, which makes it easier to form a conductive path, can effectively improve the conductive properties of the composite powder, and reduce the amount of carbon black used, while also making the dispersion of the array carbon nanotubes better; on the other hand, by making the surface of the carbon black negatively charged and the surface of the carbon nanotubes positively charged, the positive and negative charges attract each other, thereby improving the dispersion of the carbon nanotubes and carbon black in the composite powder, and improving the conductive properties of the composite powder, so that when the composite powder is used as a conductive agent, it can be directly added to the system in the form of powder, and it is very easy to disperse into various systems, that is, directly obtain a mixed powder of carbon black and carbon nanotubes, the process is simple and easy to operate, and is conducive to industrial production.
[0112] In the second aspect, based on the preparation process of the above-mentioned composite powder, an embodiment of the present application provides a composite powder, which includes: modified carbon black and modified array carbon nanotubes, wherein the surface of the modified carbon black is negatively charged, the surface of the modified array carbon nanotubes is positively charged, and the negative charge is bonded to the positive charge.
[0113] In the application, the mass ratio of the modified carbon black to the modified array carbon nanotubes can be in the range of 90-98:2-10. Preferably, the mass ratio of the modified carbon black to the modified array carbon nanotubes is 95:5. Thus, the use of a small amount of array carbon nanotubes can significantly improve the conductivity of carbon black and significantly reduce the amount of carbon black used.
[0114] The oil absorption of the composite powder may range from 120 to 220 mg / 100 g, and for example, the oil absorption of the composite powder may be 120 mg / 100 g, 140 mg / 100 g, 160 mg / 100 g, 180 mg / 100 g, 200 mg / 100 g or 220 mg / 100 g, etc. Thus, the wettability is good, so that the composite powder can be better dispersed in other systems, and the dispersibility of the composite powder is improved.
[0115] The resistivity of the composite powder may be in the range of 80-140 mΩ·cm. For example, the resistivity of the composite powder may be 80 mΩ·cm, 90 mΩ·cm, 100 mΩ·cm, 110 mΩ·cm, 120 mΩ·cm or 140 mΩ·cm, etc. Therefore, the composite powder has good conductivity.
[0116] The specific surface area of the composite powder can range from 50-150m 2 / g, for example, the resistivity of the composite powder can be 50m 2 / g, 70m 2 / g, 90m 2 / g, 120m 2 / g, 140m 2 / g or 150m 2 / g, etc. Therefore, the specific surface area of the composite powder is smaller and the dispersion performance is better.
[0117] It should be noted that the modified carbon black, modified array carbon nanotubes, etc. in the embodiments of the present application can refer to the above embodiments and will not be described in detail here.
[0118] The embodiment of the present application provides a composite powder, which is composed of modified carbon black with a negative charge and modified array carbon nanotubes with a positive charge. The positive and negative charges attract each other, which can improve the dispersion performance of the array carbon nanotubes and carbon black in the composite powder and improve the conductivity of the composite powder. At the same time, the modified array carbon nanotubes can reduce the amount of modified carbon black while improving the conductivity of the composite powder. Moreover, when the composite powder is used as a conductive agent, it can be directly added to the system in the form of powder, and it is very easy to disperse in various systems, which is simple and easy to implement.
[0119] The following uses a number of specific examples to illustrate the preparation methods and applications of the composite powders provided in the examples and comparative examples of the present application.
[0120] 1. Embodiments of the composite powder and preparation method thereof of the present application:
[0121] Example 1
[0122] 1. Preparation of carbon black with negative charge on the surface:
[0123] (1). Selection and pretreatment of carbon black:
[0124] Select N326 with a powder particle size of 100-20000nm and a resistivity of 0.2Ω·cm, place N326 in HCl with a molar concentration of 0.7mol / L, pretreat at 70°C for 1h, filter and wash until the filtrate is neutral, and then dry at 110°C for 19h to obtain N326 purified by concentrated HCl.
[0125] (2). Carbon black surface treatment:
[0126] The N326 purified by concentrated HCl was added to a PSS aqueous solution with a concentration of 0.003 g / mL (the mass volume ratio of the N326 purified by concentrated HCl to the PSS aqueous solution was 1 g:8 mL), and ultrasonic treatment was performed at a frequency of 10 Hz for 0.2 h using an ultrasonicator. The solution was stirred at a stirring speed of 100 r / min at room temperature for 1 h, and then placed in a water bath at 20°C for 2 h to obtain a PSS non-covalently modified N326 aqueous solution. The solution was filtered and washed to obtain PSS non-covalently modified N326.
[0127] (3). Preparation of modified carbon black:
[0128] The PSS non-covalently modified N326 was dispersed in a 0.0005 M NaCl solution (the dispersion concentration of N326 in the NaCl solution was 0.001 mg / mL), and ultrasonicated at a frequency of 10 Hz for 0.1 h to obtain N326 with a negative charge on the surface.
[0129] 2. Preparation of carbon nanotubes with positive surface charge:
[0130] (1) Select carbon nanotube arrays with an aspect ratio of 5000-15000 and a Raman ID / IG of 0.8-1.3, and use HCl to acidify the carbon nanotube arrays to obtain carbon nanotube arrays purified by concentrated HCl.
[0131] (2). Surface treatment of carbon nanotubes:
[0132] The array carbon nanotubes purified by concentrated HCl were added to the APTES aqueous solution (the mass volume ratio of the array carbon nanotubes purified by concentrated HCl to the APTES aqueous solution was 1 g:10 mL, and the concentration of the APTES aqueous solution was 0.01 wt%), and ultrasonic treatment was performed at a frequency of 20 Hz for 0.5 h using an ultrasonicator, followed by magnetic stirring at a stirring speed of 200 r / min for 2 h. The solution was placed in a water bath at 35° C. and allowed to stand for 4 h to obtain a uniformly dispersed array carbon nanotube aqueous solution, which was then centrifuged several times and dried to obtain APTES-modified array carbon nanotubes.
[0133] (3). Preparation of modified array carbon nanotubes:
[0134] The APTES-modified carbon nanotube arrays were dispersed in a NaCl solution with a molar mass of 0.001 M (the dispersion concentration of the APTES-modified carbon nanotube arrays in the NaCl solution was 0.01 mg / mL), and then ultrasonicated at a frequency of 20 Hz for 0.5 h to obtain carbon nanotube arrays with positive charges on the surface.
[0135] 3. Preparation of composite powder:
[0136] The above-treated carbon black with negative charge on the surface and the array carbon nanotubes with positive charge on the surface are mixed together with Cr 2 O 3 The raw materials are sent into the tank of the mixing mechanism through the feed port of the air flow pulverizing equipment. The fully mixed raw materials enter the gas pulverizer under the action of the mixing mechanism. The gas pulverizer uses 2 times supersonic air flow for pulverization. After pulverization, the first cyclone separator separates the Cr 2 O 3 The second cyclone separator collects the crushed composite powder.
[0137] Example 2
[0138] 1. Preparation of carbon black with negative charge on the surface:
[0139] (1). Selection and pretreatment of carbon black:
[0140] Select N326 with a particle size of 100-20000nm and a resistivity of 1Ω·cm, and place N326 in a H solution with a molar concentration of 0.8mol / L. 2 SO 4 The mixture was pretreated at 80 °C for 1.5 h, filtered and washed until the filtrate was neutral, and then dried at 115 °C for 20 h to obtain concentrated H 2 SO 4 Purified N326.
[0141] (2). Carbon black surface treatment:
[0142] Concentrated H 2 SO 4 The purified N326 was added to a 0.004 g / mL PSS aqueous solution (concentrated H 2 SO 4The mass volume ratio of the purified N326 to the PSS aqueous solution is 1 g:9 mL), and the solution is ultrasonically treated at a frequency of 15 Hz for 0.3 h. The solution is stirred for 1.5 h at a stirring speed of 150 r / min using an electric stirrer, and then placed in a water bath at 25°C for 3 h to obtain a PSS non-covalently modified N326 aqueous solution, which is then filtered and washed to obtain PSS non-covalently modified N326.
[0143] (3). Preparation of modified carbon black:
[0144] The PSS non-covalently modified N326 was dispersed in a 0.001 M NaCl solution (the dispersion concentration of N326 in the NaCl solution was 0.01 mg / mL), and ultrasonicated at a frequency of 15 Hz for 0.5 h using an ultrasonicator to obtain N326 with a negative charge on the surface.
[0145] 2. Preparation of carbon nanotubes with positive surface charge:
[0146] (1) Select carbon nanotube arrays with an aspect ratio of 5000-15000 and a Raman ID / IG of 0.8-1.3, and use concentrated H 2 SO 4 The array carbon nanotubes were treated with acid to obtain concentrated H 2 SO 4 Purified carbon nanotube arrays.
[0147] (2). Surface treatment of carbon nanotubes:
[0148] After concentrated H 2 SO 4 The purified array carbon nanotubes were added to the APTES aqueous solution (H 2 SO 4 The mass volume ratio of the purified array carbon nanotubes to the APTES aqueous solution is 1g:50mL, and the concentration of the APTES aqueous solution is 0.1wt%). The solution is ultrasonically treated at a frequency of 40Hz for 1h, and then stirred electrically at a stirring speed of 700r / min for 7h. The solution is placed in a 40°C water bath and allowed to stand for 7h to obtain a uniformly dispersed array carbon nanotube aqueous solution, which is then centrifuged multiple times and dried to obtain APTES-modified array carbon nanotubes.
[0149] (3). Preparation of modified array carbon nanotubes:
[0150] The APTES-modified carbon nanotube arrays were dispersed in a 0.01 M KCl solution (the dispersion concentration of the APTES-modified carbon nanotube arrays in the KCl solution was 0.1 mg / mL), and then ultrasonicated at a frequency of 30 Hz for 0.7 h to obtain carbon nanotube arrays with positive charges on the surface.
[0151] 3. Preparation of composite powder:
[0152] The above-treated carbon black with negative charge on the surface and the array carbon nanotubes with positive charge on the surface are mixed together with Cr 2 O 3 The raw materials are sent into the tank of the mixing mechanism through the feed port of the air flow pulverizing equipment. The fully mixed raw materials enter the gas pulverizer under the action of the mixing mechanism. The gas pulverizer uses 3 times supersonic air flow for pulverization. After pulverization, the first cyclone separator separates the Cr 2 O 3 The second cyclone separator collects the crushed composite powder.
[0153] Example 3
[0154] 1. Preparation of carbon black with negative charge on the surface:
[0155] (1). Selection and pretreatment of carbon black:
[0156] Select N326 with a particle size of 100-20000nm and a resistivity of 10Ω·cm, and place N326 in a H solution with a molar concentration of 0.9mol / L. 3 PO 4 The mixture was pretreated at 85 °C for 2 h, filtered and washed until the filtrate was neutral, and then dried at 120 °C for 21 h to obtain concentrated H 3 PO 4 Purified N326.
[0157] (2). Carbon black surface treatment:
[0158] Concentrated H 3 PO 4 The purified N326 was added to a 0.005 g / mL SDS aqueous solution (concentrated H 3 PO 4 The mass volume ratio of the purified N326 to the SDS aqueous solution is 1 g:10 mL), and the solution is ultrasonically treated at a frequency of 20 Hz for 0.4 h. The solution is stirred at a stirring speed of 200 r / min at room temperature with magnetic stirring, and then placed in a 30°C water bath for 4 h to obtain an SDS non-covalently modified N326 aqueous solution, which is filtered and washed to obtain SDS non-covalently modified N326.
[0159] (3). Preparation of modified carbon black:
[0160] The SDS non-covalently modified N326 was dispersed in a 0.0015 M NaCl solution (the dispersion concentration of N326 in the NaCl solution was 0.015 mg / mL), and ultrasonicated at a frequency of 20 Hz for 1 h to obtain N326 with a negative charge on the surface.
[0161] 2. Preparation of carbon nanotubes with positive surface charge:
[0162] (1) Select carbon nanotube arrays with an aspect ratio of 5000-15000 and a Raman ID / IG of 0.8-1.3, and use concentrated H 3 PO 4 The array carbon nanotubes were treated with acid to obtain concentrated H 3 PO 4 Purified carbon nanotube arrays.
[0163] (2). Surface treatment of carbon nanotubes:
[0164] After concentrated H 3 PO 4 The purified carbon nanotube arrays were added to an APTES aqueous solution (concentrated H 3 PO 4 The mass volume ratio of the purified array carbon nanotubes to the APTES aqueous solution is 1g:80mL, and the concentration of the APTES aqueous solution is 1wt%), and an ultrasonic device is used to perform ultrasonic treatment at a frequency of 60Hz for 10h, followed by magnetic stirring at a stirring speed of 1000r / min for 12h, and the solution is placed in a 50°C water bath and allowed to stand for 10h to obtain a uniformly dispersed array carbon nanotube aqueous solution, which is then centrifuged multiple times and dried to obtain APTES-modified array carbon nanotubes.
[0165] (3). Preparation of modified array carbon nanotubes:
[0166] APTES-modified carbon nanotube arrays were dispersed in 0.1 M CaCl 2 Solution (APTES modified carbon nanotube arrays in CaCl 2 The dispersion concentration in the solution is 1 mg / mL), and then an ultrasonic device is used to perform ultrasonic treatment at a frequency of 50 Hz for 0.8 h to obtain an array of carbon nanotubes with positive charges on the surface.
[0167] 3. Preparation of composite powder:
[0168] The above-treated carbon black with negative charge on the surface and the array carbon nanotubes with positive charge on the surface are mixed together with Cr 2 O 3The raw materials are sent into the tank of the mixing mechanism through the feed port of the air flow pulverizing equipment. The fully mixed raw materials enter the gas pulverizer under the action of the mixing mechanism. The gas pulverizer uses 4 times supersonic air flow for pulverization. After pulverization, the first cyclone separator separates the Cr 2 O 3 The second cyclone separator collects the crushed composite powder.
[0169] Example 4
[0170] 1. Preparation of carbon black with negative charge on the surface:
[0171] (1). Selection and pretreatment of carbon black:
[0172] Select N326 with a powder particle size of 100-20000nm and a resistivity of 20Ω·cm, place N326 in HCl with a molar concentration of 1.0mol / L, pretreat at 90°C for 2.5h, filter and wash until the filtrate is neutral, and then dry at 123°C for 22h to obtain N326 purified by concentrated HCl.
[0173] (2). Carbon black surface treatment:
[0174] The N326 purified by concentrated HCl was added to an aqueous SDBS solution with a concentration of 0.006 g / mL (the mass volume ratio of the N326 purified by concentrated HCl to the SDBS aqueous solution was 1 g:11 mL), and ultrasonic treatment was performed at a frequency of 25 Hz for 0.5 h using an ultrasonicator. The solution was stirred at room temperature at a stirring speed of 250 r / min for 2.5 h, and then placed in a water bath at 33° C. for 4.5 h to obtain an aqueous solution of N326 non-covalently modified with SDBS. The solution was filtered and washed to obtain N326 non-covalently modified with SDBS.
[0175] (3). Preparation of modified carbon black:
[0176] The SDBS non-covalently modified N326 was dispersed in a 0.002 M NaCl solution (the dispersion concentration of N326 in the NaCl solution was 0.02 mg / mL), and ultrasonicated for 1.3 h at a frequency of 25 Hz using an ultrasonicator to obtain N326 with a negative charge on the surface.
[0177] 2. Preparation of carbon nanotubes with positive surface charge:
[0178] (1) Select carbon nanotube arrays with an aspect ratio of 5000-15000 and a Raman ID / IG of 0.8-1.3, and acidify the carbon nanotube arrays with concentrated HCl to obtain carbon nanotube arrays purified by concentrated HCl.
[0179] (2). Surface treatment of carbon nanotubes:
[0180] The array carbon nanotubes purified by concentrated HCl were added to the KH-550 aqueous solution (the mass volume ratio of the array carbon nanotubes purified by concentrated HCl to the KH-550 aqueous solution was 1 g:100 mL, and the concentration of the KH-550 aqueous solution was 3 wt%), and ultrasonic treatment was performed at a frequency of 70 Hz for 15 h using an ultrasonicator, followed by electric stirring at room temperature for 18 h at a stirring speed of 2000 r / min, and the solution was placed in a water bath at 60° C. and allowed to stand for 15 h to obtain a uniformly dispersed array carbon nanotube aqueous solution, which was then centrifuged several times and dried to obtain KH-550-modified array carbon nanotubes.
[0181] (3). Preparation of modified array carbon nanotubes:
[0182] The KH-550 modified carbon nanotube arrays were dispersed in a 1 M NaCl solution (the dispersion concentration of the KH-550 modified carbon nanotube arrays in the NaCl solution was 3 mg / mL), and then ultrasonicated at 70 Hz for 1.0 h to obtain carbon nanotube arrays with positive charges on the surface.
[0183] 3. Preparation of composite powder:
[0184] The above-treated carbon black with negative charge on the surface and the array carbon nanotubes with positive charge on the surface are mixed together with Cr 2 O 3 The raw materials are sent into the tank of the mixing mechanism through the feed port of the air flow pulverizing equipment. The fully mixed raw materials enter the gas pulverizer under the action of the mixing mechanism. The gas pulverizer uses 5 times supersonic air flow to pulverize. After pulverization, the first cyclone separator separates the Cr 2 O 3 The second cyclone separator collects the crushed composite powder.
[0185] Example 5
[0186] 1. Preparation of carbon black with negative charge on the surface:
[0187] (1). Selection and pretreatment of carbon black:
[0188] Select N326 with a particle size of 100-20000nm and a resistivity of 30Ω·cm, and place N326 in a H solution with a molar concentration of 1.1mol / L. 2 SO 4 The mixture was pretreated at 95 °C for 2.8 h, filtered and washed until the filtrate was neutral, and then dried at 128 °C for 23 h to obtain concentrated H 2 SO 4 Purified N326.
[0189] (2). Carbon black surface treatment:
[0190] Concentrated H 2 SO 4 The purified N326 was added to a 0.007 g / mL PSS aqueous solution (concentrated H 2 SO 4 The mass volume ratio of the purified N326 to the PSS aqueous solution is 1 g:12 mL), and the solution is ultrasonically treated at a frequency of 28 Hz for 0.6 h. The solution is stirred at a stirring speed of 280 r / min at room temperature with magnetic stirring for 3 h. The solution is placed in a water bath at 38°C and allowed to stand for 5 h to obtain a PSS non-covalently modified N326 aqueous solution. The solution is filtered and washed to obtain PSS non-covalently modified N326.
[0191] (3). Preparation of modified carbon black:
[0192] The PSS non-covalently modified N326 was dispersed in a 0.0025 M NaCl solution (the dispersion concentration of N326 in the NaCl solution was 0.025 mg / mL), and ultrasonically treated at a frequency of 28 Hz for 1.7 h using an ultrasonicator to obtain N326 with a negative charge on the surface.
[0193] 2. Preparation of carbon nanotubes with positive surface charge:
[0194] (1) Select carbon nanotube arrays with an aspect ratio of 5000-15000 and a Raman ID / IG of 0.8-1.3, and use H 2 SO 4 The array carbon nanotubes were treated with acid to obtain H 2 SO 4 Purified carbon nanotube arrays.
[0195] (2). Surface treatment of carbon nanotubes:
[0196] After concentrated H 2 SO 4 The purified carbon nanotube arrays were added to an APTES aqueous solution (concentrated H 2 SO 4 The mass volume ratio of the purified array carbon nanotubes to the APTES aqueous solution is 1g:120mL, and the concentration of the APTES aqueous solution is 6wt%), and an ultrasonic device is used to perform ultrasonic treatment at a frequency of 80Hz for 20h, followed by magnetic stirring at a stirring speed of 3000r / min for 20h, and the solution is placed in a water bath at 65°C and allowed to stand for 20h to obtain a uniformly dispersed array carbon nanotube aqueous solution, which is then centrifuged multiple times and dried to obtain APTES-modified array carbon nanotubes.
[0197] (3). Preparation of modified array carbon nanotubes:
[0198] The APTES-modified carbon nanotube arrays were dispersed in a 1.5 M KCl solution (the dispersion concentration of the APTES-modified carbon nanotube arrays in the KCl solution was 6 mg / mL), and then ultrasonicated at 80 Hz for 1.5 h to obtain carbon nanotube arrays with positive charges on the surface.
[0199] 3. Preparation of composite powder:
[0200] The above-treated carbon black with negative charge on the surface and the array carbon nanotubes with positive charge on the surface are mixed together with Cr 2 O 3 The raw materials are sent into the tank of the mixing mechanism through the feed port of the air flow pulverizing equipment. The fully mixed raw materials enter the gas pulverizer under the action of the mixing mechanism. The gas pulverizer uses 6 times supersonic air flow for pulverization. After pulverization, the first cyclone separator separates the Cr 2 O 3 The second cyclone separator collects the crushed composite powder.
[0201] Example 6
[0202] 1. Preparation of carbon black with negative charge on the surface:
[0203] (1). Selection and pretreatment of carbon black:
[0204] Select N326 with a particle size of 100-20000nm and a resistivity of 50Ω·cm, and place N326 in a H solution with a molar concentration of 1.2mol / L. 3 PO 4 The product was pretreated at 100 °C for 3 h, filtered and washed until the filtrate was neutral, and then dried at 130 °C for 24 h to obtain concentrated H 3 PO 4 Purified N326.
[0205] (2). Carbon black surface treatment:
[0206] Concentrated H 3 PO 4 The purified N326 was added to a 0.008 g / mL PSS aqueous solution (concentrated H 3 PO 4The mass volume ratio of the purified N326 to the PSS aqueous solution is 1 g:13 mL), and the solution is ultrasonically treated at a frequency of 30 Hz for 0.7 h. The solution is stirred at room temperature at a stirring speed of 300 r / min for 4 h, and then placed in a 40°C water bath for 6 h to obtain a PSS non-covalently modified N326 aqueous solution. The solution is filtered and washed to obtain PSS non-covalently modified N326.
[0207] (3). Preparation of modified carbon black:
[0208] The PSS non-covalently modified N326 was dispersed in a 0.003 M NaCl solution (the dispersion concentration of N326 in the NaCl solution was 0.03 mg / mL), and ultrasonically treated at a frequency of 30 Hz for 2 h to obtain N326 with a negative charge on the surface.
[0209] 2. Preparation of carbon nanotubes with positive surface charge:
[0210] (1) Select carbon nanotube arrays with an aspect ratio of 5000-15000 and a Raman ID / IG of 0.8-1.3, and use concentrated H 3 PO 4 The array carbon nanotubes were treated with acid to obtain concentrated H 3 PO 4 Purified carbon nanotube arrays.
[0211] (2). Surface treatment of carbon nanotubes:
[0212] After concentrated H 3 PO 4 The purified carbon nanotube arrays were added to an APTES aqueous solution (concentrated H 3 PO 4 The mass volume ratio of the purified array carbon nanotubes to the APTES aqueous solution is 1g:150mL, and the concentration of the APTES aqueous solution is 10wt%), and an ultrasonic device is used to perform ultrasonic treatment at a frequency of 100Hz for 24h, followed by magnetic stirring or electric stirring at a stirring speed of 4000r / min for 24h, and the solution is placed in a 70°C water bath and allowed to stand for 24h to obtain a uniformly dispersed array carbon nanotube aqueous solution, which is then centrifuged multiple times and dried to obtain APTES-modified array carbon nanotubes.
[0213] (3). Preparation of modified array carbon nanotubes:
[0214] APTES modified carbon nanotube arrays were dispersed in 2 M CaCl 2 Solution (APTES modified carbon nanotube arrays in CaCl 2The dispersion concentration in the solution is 10 mg / mL), and then an ultrasonic device is used to perform ultrasonic treatment at a frequency of 100 Hz for 2 hours to obtain an array of carbon nanotubes with positive charges on the surface.
[0215] 3. Preparation of composite powder:
[0216] The above-treated carbon black with negative charge on the surface and the array carbon nanotubes with positive charge on the surface are mixed together with Cr 2 O 3 The raw materials are sent into the tank of the mixing mechanism through the feed port of the air flow pulverizing equipment. The fully mixed raw materials enter the gas pulverizer under the action of the mixing mechanism. The gas pulverizer uses 2 times supersonic air flow for pulverization. After pulverization, the first cyclone separator separates the Cr 2 O 3 The second cyclone separator collects the crushed composite powder.
[0217] 2. Comparative Example Single-walled carbon nanotube conductive slurry and preparation method thereof:
[0218] Comparative Example 1
[0219] Compared with Example 1, unmodified carbon black is used, and the surface of the unmodified carbon black has no negative charge.
[0220] Comparative Example 2
[0221] Compared with Example 1, unmodified carbon nanotubes are used, and the surface of the unmodified carbon nanotubes has no positive charge.
[0222] Comparative Example 3
[0223] Compared with Example 1, the preparation process of the composite powder does not adopt the air flow pulverization process.
[0224] The following provides a lithium ion battery using the composite powder of the present application embodiment:
[0225] 1. Preparation of positive electrode sheet:
[0226] The positive electrode slurry was prepared according to the mass ratio of lithium iron phosphate (LFP), polyvinylidene fluoride (PVDF) and composite powder of 94:2:0.6, and then N-methylpyrrolidone was added to adjust the solid content to 55wt%, and then put into a double planetary mixer for vacuum high-speed homogenization. The revolution speed was adjusted to 2000RPM and the rotation speed was adjusted to 800RPM. After homogenization for 20 minutes, it was coated on the positive electrode collector and dried at 80°C to obtain the positive electrode sheet. The sheet resistance of the positive electrode sheet was tested under a pressure of 40KG. The test results are shown in Table 1.
[0227] 2. Assembly and testing of lithium-ion batteries
[0228] The positive electrode sheet was cut as the positive electrode, and the lithium sheet was used as the negative electrode to prepare a CR2032 button battery, which was tested on a Blue Electric test system.
[0229] The charge and discharge conditions are set as follows: charge to a cut-off voltage of 4.2 V, discharge to a cut-off voltage of 2.5 V, and cycle at 0.1C, 0.5C, 1C, 3C, and 5C for 5 weeks each, to obtain the 0.1C discharge capacity and 5C discharge capacity of the CR2032 button battery. The test results are shown in Table 1.
[0230] Table 1
[0231]
[0232] As can be seen from Table 1, compared with Comparative Example 1, the carbon black added in Example 1 of the present application is not modified, resulting in no negative charge on its surface, which cannot attract the array carbon nanotubes with positive charges on the surface, making it difficult to form a conductive path, and the amount of carbon black cannot be reduced. The dispersion of the array carbon nanotubes is relatively poor, which reduces the overall conductivity of the composite powder. As a result, the sheet resistance of the positive electrode sheet is high, the 0.1C and 5C discharge capacities of the battery are low, and the service life of the lithium-ion battery is short and the effect is poor.
[0233] Compared with Comparative Example 2, the carbon nanotubes added in Example 1 of the present application are not modified, and are neither array carbon nanotubes nor have positive charges on their surfaces, and cannot attract each other with carbon black with negative charges on the surface, making it difficult to form a conductive path, and the amount of carbon black cannot be reduced. The dispersion of the array carbon nanotubes is relatively poor, which reduces the overall conductivity of the composite powder. As a result, the sheet resistance of the positive electrode sheet is high, the 0.1C and 5C discharge capacities of the battery are low, and the service life of the lithium-ion battery is short and the effect is poor.
[0234] Compared with Example 3, Example 1 of the present application does not use the airflow pulverization process to pulverize the composite powder in Example 3, so that the amount of carbon black cannot be significantly reduced, and the dispersion of the array carbon nanotubes is not so good, which slightly reduces the overall conductivity of the composite powder. As a result, the sheet resistance of the positive electrode sheet is high, the 0.1C and 5C discharge capacities of the lithium-ion battery are both low, and the service life of the lithium-ion battery is short and the effect is poor.
[0235] Compared with Example 1, Examples 2-6 of the present application are only slightly different in the formula of the composite powder and some parameters in the process. Therefore, compared with Comparative Examples 1-3, Examples 2-6 can reduce the amount of carbon black as much as possible, and the dispersion performance of the array carbon nanotubes is good, so that the overall conductivity of the composite powder is significantly improved. Therefore, the sheet resistance of the positive electrode sheet is low, the 0.1C and 5C discharge capacities of the lithium-ion battery are both high, and the lithium-ion battery has a long service life and good effect.
[0236] Only the contents related to the invention are introduced here. The rest can be obtained by referring to the relevant technology and will not be described in detail here.
[0237] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A composite powder, characterized in that: include: Modified carbon black, wherein the modified carbon black is obtained by the following steps: mixing carbon black with an acid solution and treating it to obtain acidified carbon black, adding the acidified carbon black into an anionic surfactant aqueous solution and treating it to obtain anionic surfactant-modified carbon black, dispersing the anionic surfactant-modified carbon black in a first salt solution and treating it to obtain modified carbon black with a negative charge on the surface; Modified array carbon nanotubes, wherein the modified array carbon nanotubes are obtained by the following steps: mixing array carbon nanotubes with acid solution and treating them to obtain acidified array carbon nanotubes, adding the acidified array carbon nanotubes into an aqueous solution of a coupling agent containing amino groups and treating them to obtain carbon nanotubes modified by the coupling agent containing amino groups, dispersing the carbon nanotubes modified by the coupling agent containing amino groups in a second salt solution and treating them to obtain modified array carbon nanotubes with positive charges on the surface; The negative charges in the modified carbon black are used to attract the positive charges in the modified array carbon nanotubes.
2. The composite powder according to claim 1, characterized in that: The step of mixing carbon black with acid solution and treating the mixture to obtain acidified carbon black comprises: Selecting conductive carbon black with a particle size range of 100-20000nm; The conductive carbon black is placed in an acid solution with a molar concentration range of 0.7-1.2 mol / L, pretreated at 70-100° C. for 1-3 hours, filtered and washed until the filtrate is neutral, and then dried at 110-130° C. for 19-24 hours to obtain the acidified carbon black.
3. The composite powder according to claim 2, characterized in that: The step of adding the acidified carbon black to an anionic surfactant aqueous solution and treating the carbon black to obtain anionic surfactant-modified carbon black, and dispersing the anionic surfactant-modified carbon black in a first salt solution and treating the carbon black to obtain a modified carbon black with a negative charge on the surface comprises: The acidified carbon black is placed in an aqueous solution of an anionic surfactant with a concentration range of 0.003-0.008 g / mL, and ultrasonically treated at a frequency of 10-30 Hz for 0.2-0.7 h. After stirring the solution at a stirring speed range of 100-300 r / min for 1-4 h, the solution is placed in a water bath at 20-40° C. and allowed to stand for 2-6 h. The solution is filtered and washed, and then dispersed in a 0.0005-0.003 M salt solution, and ultrasonically treated at a frequency of 10-30 Hz for 0.1-2 h to obtain the modified carbon black with a negative charge on the surface.
4. The composite powder according to claim 1, characterized in that: The step of mixing the array carbon nanotubes with the acid solution and treating the mixture to obtain the acidified array carbon nanotubes comprises: Selecting array carbon nanotubes with an aspect ratio ranging from 5000 to 15000 and a Raman spectrum intensity ratio ranging from 0.8 to 1.3; The array carbon nanotubes are placed in an acid solution for treatment, and then filtered, washed and dried to obtain the acidified array carbon nanotubes.
5. The composite powder according to claim 4, characterized in that: The step of adding the acidified array carbon nanotubes to an aqueous solution of a coupling agent containing amino groups and treating the mixture to obtain carbon nanotubes modified with the coupling agent containing amino groups, and dispersing the carbon nanotubes modified with the coupling agent containing amino groups in a second salt solution and treating the mixture to obtain modified array carbon nanotubes with positive charges on the surface comprises: The acidified carbon nanotubes are added to an aqueous solution of an amino-containing coupling agent, and ultrasonically treated at a frequency of 20-100 Hz for 0.5-24 hours, and stirred at a stirring speed range of 200-4000 r / min for 2-24 hours, and the solution containing the acidified array carbon nanotubes and the amino-containing coupling agent is placed in a 35-70° C. water bath for 4-24 hours, and then dried after multiple centrifugations to obtain carbon nanotubes modified with an amino-containing coupling agent; The carbon nanotubes modified by the amino-containing coupling agent are dispersed in a salt solution with a molar mass range of 0.001-2M, and ultrasonically treated at a frequency of 20-100 Hz for 0.5-2 hours to obtain the modified array carbon nanotubes with positive charges on the surface.
6. The composite powder according to any one of claims 1 to 5, characterized in that The mass ratio of the modified carbon black to the modified array carbon nanotubes is in the range of 90-98:2-10.
7. The composite powder according to claim 6, characterized in that: The oil absorption range of the composite powder is 120-220 mg / 100 g; and / or, The resistivity of the composite powder is in the range of 80-140 mΩ·cm; and / or, The specific surface area of the composite powder is in the range of 50-150 m 2 / g.
8. A lithium ion battery, characterized in that: The invention comprises the composite powder as described in any one of claims 1 to 7.
9. A method for preparing a composite powder according to any one of claims 1 to 7, characterized in that: The steps include: The modified carbon black and the modified array carbon nanotubes are mixed and pulverized to obtain the composite powder.
10. The method for preparing composite powder according to claim 9, characterized in that: The mixture of modified carbon black and modified array carbon nanotubes is pulverized by using air flow pulverizing equipment.
Citation Information
Patent Citations
Preparation method of carbon black-electrostatically adsorbed carbon nano tube conductive filler
CN105885474A
Preparation method for cellulose composite paper
CN110144762A
Composite conductive agent, preparation method thereof and conductive plastic
CN112852021A
Preparation method of graphene composite conductive slurry
CN113036143A
Composite conductive powder, preparation method thereof and lithium battery
CN114976001A